Winning Hearts and Minds: How Developing Countries Can Effectively Use Soft Power - Singh, Richa (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
This paper examines how developing countries can effectively employ soft power as a strategic tool in international relations. Traditionally associated with developed nations due to their cultural dominance, global media presence, and strong diplomatic networks, soft power defined as influence through attraction rather than coercion-can also be harnessed by less economically and militarily powerful states. The research explores how these countries can utilize cultural identity, political values, and diplomatic efforts to build international influence. Through theoretical analysis, case studies, and comparative assessment, the paper identifies key conditions and strategies that enable developing nations to cultivate and exercise soft power successfully. The study also addresses challenges such as resource constraints, governance issues, and credibility gaps, and offers policy recommendations for enhancing soft power in developing contexts. The findings suggest that with strategic investments in education, culture, technology, and global communication, developing countries can increase their international visibility and influence through soft power means.